Renascimento simbólico pós-revolução de Abril em Balada da Praia dos Cães e Alexandra Alpha, de José Cardoso Pires - Saldanha, Ana [UNESP] (My University, 2014)
Analysis of the dictatorial Portuguese period (1926-1974) in the fiction of José Cardoso Pires, taking into account the mythological-symbolic deconstruction done by this author. In this sense, we'll cover the problematization of space undertaken by the author as well as the study of symbolism and social imaginary, before and after the revolution on 25 April 1974, especially in two works: Balada da Praia dos Cães e Alexandra Alpha. We'll continue this study with a reflection on the duality historical time-time of narrative in both works, doing a parallel with a work of a Portuguese author which, in order to discuss the recent Portuguese past, also employs this same duality: Casas Pardas, by Maria Velho da Costa.
The Portuguese post-revolution imaginary
Keywords: Imaginary; Literature; Neorealist novel; Portuguese revolution; Symbols